"The word as image": survey with special reference to the twentieth century - Edworthy, S (Rhodes University, Faculty of Humanities, Department of Fine Art)
This essay is intended, firstly for those who at some time have had the urge to include words into their otherwise conventional representational images, but are deterred by the suspicion that such elements have no place in the picture plane. Secondly, it is hoped, that this dissertation will provide some understanding concerning the motivations and aims of artists, using "verbal symbols" in their visual images. At this point, I offer some explanation of the term "verbal symbols". The alphabet that we are accustomed to today differs vastly from the first writing that was invented. The naming of items nowadays is arbitrarily established and all we are left with is a name that bears no visual resemblance to the object it represents in real life. The word "house", for example, tells us nothing of the physical nature of a house. However, owing to our conditioning, the word evokes in us a mental picture of a house, even if the details of this picture will vary amongst individuals. Words then are symbols which denote, broadly speaking, objects that exist in our daily lives, without being in any way visual representations of these objects. Of course there are also words which are dependent on other words for their meaning, such as prepositions, conjunctions or suffices, but this is irrelevant to this essay.
Keywords: Symbolism in art; Art, Modern -- 20th century -- History; Art and society -- History -- 20th century; Salomon, Charlotte, 1917-1943 -- Criticism and interpretation; Kiefer, Anselm, 1945- -- Criticism and interpretation